Fabrication of covalent organic frameworks modified nanofibrous membrane for efficiently enriching and detecting the trace polychlorinated biphenyls in water. (15th May 2023) - Lv, Yuancai; Ma, Jiachen; Yu, Zhendong; Liu, Shuting; Yang, Guifang; Liu, Yifan; Lin, Chunxiang; Ye, Xiaoxia; Shi, Yongqian; Liu, Minghua
Highlights: COFs in situ grew on polyacrylonitrile membrane (PAN-SiO2 @TpPa) under room temperature. PAN-SiO2 @TpPa showed outstanding enrichment of trace PCBs in water. PAN-SiO2 @TpPa could be used to enrich the PCBs (5 ng L −1 ) in real water. Hydrophobic effect, π-π stacking and hydrogen bonding were the main mechanism. Abstract: Enriching and detecting the trace pollutants in actual matrices are critical to evaluating the water quality. Herein, a novel nanofibrous membrane, named PAN-SiO2 @TpPa, was prepared by in situ growing β -ketoenamine-linked covalent organic frameworks (COF-TpPa) on the aminated polyacrylonitrile (PAN) nanofibers, and adopted for enriching the trace polychlorinated biphenyls (PCBs) in various natural water body (river, lake and sea water) through the solid-phase micro-extraction (SPME) process. The resulted nanofibrous membrane owned abundant functional groups (-NH-, -OH and aromatic groups), outstandingly thermal and chemical stability, and excellent ability in extracting PCBs congeners. Based on the SPME process, the PCBs congeners could be quantitatively analyzed by the traditional gas chromatography (GC) method, with the satisfactory linear relationship (R 2 >0.99), low detection limit (LODs, 0.1∼5 ng L −1 ), high enrichment factors (EFs, 2714∼3949) and multiple recycling (>150 runs). Meanwhile, when PAN-SiO2 @TpPa was adopted in the real water samples, the low matrix effects on the enrichment of PCBs at both 5 and 50 ng L −1 over PAN-SiO2 @TpPa membrane firmly revealed the feasibility of enriching the trace PCBs in real water. Besides, the related mechanism of extracting PCBs on PAN-SiO2 @TpPa mainly involved the synergistic effect of hydrophobic effect, π-π stacking and hydrogen bonding. Graphical abstract: Image, graphical abstract